Les bibliothèques possibles - William Marx (Carnets)
To make the potentialities of any text appear, it is as simple as moving it from one library to another. This is what happens when we read a foreign text: it is then enriched by the new literary references present in the reader’s mind. Such is the mental gesture of extraction. There is also another gesture, reintegration, which can be described as follows: I extract a work from my present mental library, and I reintegrate it in its original historical, cultural and ideological environment. In this case too, a different work is revealed, because to enter a library that one does not know, a distant or ancient library, is also to enter a different mental landscape. Now, among all the possible libraries, there are some that are more possible or probable than the others: such are the probablibraries.